Public Perception of the Rain Handler at the Mandalika MotoGP International Circuit - Sulanjari, Dety Junita; Handayani, Sri; Mutiah , Susanty I; Djohar; Syaekhu, Ahmad (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2022)
The rain handler ritual is a local cultural tradition carried out from generation to generation by the community in several regions in Indonesia. This study aims to determine the public perception of the rain handler at the Mandalika MotoGP International Circuit. The location of this research is at the Mandalika International Circuit, Central Lombok, West Nusa Tenggara, while the informants in this study are the general public, especially in South Sulawesi. The data collection techniques in this study were observation, interview, and documentation techniques. Data analysis techniques in this study are data collection, data condensation, data presentation, and data verification or conclusions. The results of the study indicate that the public’s perception of the rain handler at the Mandalika MotoGP International Circuit is a “local wisdom” that has existed for a long time and was taught by the ancestors using different spells according to the customs and culture of a region. This research can be used as a reference regarding local wisdom and rituals carried out by the rain handlers at the Mandalika MotoGP Circuit, because previous research focused on the rain handler profession at celebration events only. Keywords: